American Indian politics and the american political system - WILKINS, David E (Rowman & Littlefield Pub, 2002)
Now in its third edition, American Indian Politics is the most comprehensive study written from a political science perspective that analyzes the structures and functions of indigenous governments (including Alaskan Native communities and Hawaiian Natives) and the distinctive legal and political rights these nations exercise internally, while also examining the fascinating intergovernmental relationship that exists between native nations, the states, and the federal government. The third edition contains a number of important modifications. First, it is now co-authored by Heidi Kiiwetinepinesiik Stark, who brings a spirited new voice to the study. Second, it contains ample discussion of how President ObamaOs election has altered the dynamics of Indian Country politics and law. Third, it contains more discussion of women's issues, several new vignettes, an updated timeline, new photographs, and updated charts, tables, and figures.